Recent Advances in Silent Gene Cluster Activation in Streptomyces - Liu, Zhenyu; Zhao, Yatong; Huang, Chaoqun; Luo, Yunzi (Frontiers in Bioengineering and Biotechnology, 2021)
Natural products (NPs) are a critical source of drug molecules for decades, and about two-thirds of natural antibiotics are produced by Actinobacteria. Actinobacteria have a large number of secondary metabolism biosynthetic gene clusters (SM-BGCs) that may encode NPs, but most of the BGCs are silent in the original actinomycetes under laboratory conditions. Hence, activation of these silent BGCs is the key to current natural products discovery research. In this review, we described the commonly used strategies for silent BGC activation in Actinomycetes from two aspects. One focused on the strategies applied in heterologous host, including methods to clone and reconstruct BGCs along with advances in chassis engineering; and the other focused on methods applied in native host which includes engineering of promoters, regulatory factors, and ribosomes. With the metabolic network being elucidated more comprehensively and methods optimized more high-thoroughly, the discovery of NPs will be greatly accelerated.